Chitosan-carrageenan polyelectrolyte complex matrix as new protein/peptide drug carrier. - Chow, Sharan Mei Wei. (2009)
The oral route administration of protein and peptide drug has been limited by low bioavailability due to extensive hydrolysis and proteolytic enzymes activity in the gastrointestinal (GI) tract. Hence, chitosan-κ-carrageenan polyelectrolyte complex matrix that exhibit pH-dependent swelling characteristic is introduced as a biodegradable vesicle for oral administration. The chitosan-carrageenan particles was synthesized using chitosan and κ-carrageenan solutions at 500rpm. A model protein, bovine serum albumin (BSA), was loaded into the particles synthesized by incubating the particles in protein solution at pH4.5. The release of protein from the freeze-dried polyplex particles were tested in simulated gastric fluid (SGF pH1.2) and simulated intestinal fluid (SIF pH7.5) at different time intervals. Within 4 hours incubation, the particles released only 7% of loaded protein in SGF but higher amount of loaded protein (25%) in SIF, which shows higher stability of the polyplex particles in gastric environment. To mimic the physiological GI conditions, the particles were first incubated in SGF for 4 hours and were transferred to SIF for additional release study. 2% of BSA release was detected after 4 hour incubation in SGF and 12% of total release was attained after another 4 hour incubation in SIF. In addition, another batch of BSA encapsulated particles was prepared via incorporation method and tested for the protein release profiles in identical procedures. The results suggest that a better protein loading efficiency is attained. The findings from this project is encouraging and offer good potential for the further investigation of chitosan-carrageenan polyplex particles as new protein drug carrier.